Nutritional Interventions in Cancer Cachexia: Evidence and Perspectives From Experimental Models - van de Worp, Wouter R. P. H.; Schols, Annemie M. W. J.; Theys, Jan; van Helvoort, Ardy; Langen, Ramon C. J. (Frontiers in Nutrition, 2020)
Cancer cachexia is a complex metabolic syndrome characterized by involuntary skeletal muscle loss and is associated with poor clinical outcome, decreased survival and negatively influences cancer therapy. No curative treatments are available for cancer cachexia, but nutritional intervention is recommended as a cornerstone of multimodal therapy. Optimal nutritional care is pivotal in the treatment of cancer cachexia, and the effects of nutrients may extend beyond provision of adequate energy uptake, targeting different mechanisms or metabolic pathways that are affected or deregulated by cachexia. The evidence to support this notion derived from nutritional intervention studies in experimental models of cancer cachexia is systematically discussed in this review. Moreover, experimental variables and readout parameters to determine skeletal muscle wasting and cachexia are methodologically evaluated to allow critical comparison of similar studies. Single- and multinutrient intervention studies including qualitative modulation of dietary protein, dietary fat, and supplementation with specific nutrients, such as carnitine and creatine, were reviewed for their efficacy to counteract muscle mass loss and its underlying mechanisms in experimental cancer cachexia. Numerous studies showed favorable effects on impaired protein turnover and related metabolic abnormalities of nutritional supplementation in parallel with a beneficial impact on cancer-induced muscle wasting. The combination of high quality nutrients in a multinutrient approach appears specifically promising, preferentially as a multimodal intervention, although more studies investigating the optimal quantity and combination of nutrients are needed. During the review process, a wide variation in timing, duration, dosing and route of supplementation, as well as a wide variation in animal models were observed. Better standardization in dietary design, and the development of experimental models that better recapitulate the etiology of human cachexia, will further facilitate successful translation of experimentally-based multinutrient, multimodal interventions into clinical practice.